SLC27A5 inhibits cancer stem cells by inducing alternative polyadenylation of METTL14 in hepatocellular carcinoma - Xin Tang; Junji Tao; Yuanyuan Liu; Deao Gong; Xuefeng Shan; Kai Wang; Ni Tang (Genes and Diseases)
Solute carrier family 27 member 5 (SLC27A5/FATP5) is a liver-specific metabolic enzyme that plays a crucial role in fatty acid transport and bile acid metabolism. Deficiency of SLC27A5 promotes the progression of hepatocellular carcinoma (HCC) and is strongly associated with a poor prognosis. SLC27A5 exhibits noncanonical functions beyond its metabolic role; however, its specific mechanisms in hepatocarcinogenesis remain elusive and are therefore investigated in this study. Immunoprecipitation-mass spectrometry analysis showed that SLC27A5-interacting proteins were significantly enriched in alternative polyadenylation (APA). RNA-sequencing data provided evidence that SLC27A5 plays a global role in regulating APA events in HCC. Mechanistically, SLC27A5 facilitates the usage of the proximal polyadenylation site of METTL14 by downregulating the expression of the APA-associated factor PABPC1, resulting in the shortening of the METTL14-3′UTR and the conversion of METTL14-UL to METTL14-US. In contrast to METTL14-UL, METTL14-US escapes the inhibitory effect of miRNA targeting, leading to increased METTL14 expression. METTL14-US upregulation by SLC27A5 suppressed the stemness of HCC. Therefore, low levels of SLC27A5 and METTL14 may serve as reliable biomarkers for identifying poor prognosis in patients with HCC. In conclusion, SLC27A5/PABPC1 inhibits HCC stemness via APA-regulated expression of METTL14, providing potential avenues for the development of novel therapeutic strategies.